Study of Ornamental Fish in Lalitpur, Nepal - Jha, Bandana; Prasad, Archana (Nepalese Journal of Zoology, 2015)
This work has been done from 2068 to 2069.The main theme of the survey was to find out the Aquarium fish interest among people, highest and lowest price of different fishes, feeding criteria, socio economic condition of aquarium fish trade. Survey points out that few shops are in Lalitpur. Gold fish varieties are famous among the people. Only artificial feed was given to the fishes. Increasing number of shops and satisfactory response regarding this business shows better socio economic condition regarding this sector.